2020
DOI: 10.1177/1120672120968740
|View full text |Cite
|
Sign up to set email alerts
|

Association between central retinal thickness and low luminance visual acuity in early age-related macular degeneration

Abstract: Purpose/Aim: To examine whether central retinal thickness (CRT) is related to mesopic visual acuity (VA) and low luminance deficit (LLD, difference between photopic and mesopic VA) in eyes with early and intermediate age-related macular degeneration (AMD). Materials and Methods: In a cross-sectional study, 50 pseudophakic subjects older than 63 years were divided into three groups (no AMD, early AMD and intermediate AMD). Spectral domain optical coherence tomography (SD-OCT) was used to measure CRT in the 1 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is necessary to do a visual acuity test compared to CRT under photopic and mesopic luminance conditions and then compared with normal conditions which with increasing age are also known to change physiologically in these functions. 18 Subsequent studies are slightly contradictory but some points are linear with the above comparison. The study of Danis et al, 2015 showed a negative correlation between CRT and changes in BCVA in cases of exudative AMD at day 90 and day 180 post anti-VEGF injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to do a visual acuity test compared to CRT under photopic and mesopic luminance conditions and then compared with normal conditions which with increasing age are also known to change physiologically in these functions. 18 Subsequent studies are slightly contradictory but some points are linear with the above comparison. The study of Danis et al, 2015 showed a negative correlation between CRT and changes in BCVA in cases of exudative AMD at day 90 and day 180 post anti-VEGF injection.…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors that causes this is the damage to the function of the RPE itself which results in damage to central visual acuity so that it is necessary to test the function of the RPE and other functional visual tests. 17,18 Damage to the RPE function will result in other visual disturbances. It should be noted that mesopic or low illuminance, low luminance deficit (LLD) and the difference between photopic and mesopic visual acuity will be impaired in patients even from early AMD.…”
Section: Discussionmentioning
confidence: 99%
“…CMT is an important indicator of OCT for observing the morphological structure and pathological changes of the macular area. An increase in CMT is related to the deterioration of retinal function and can damage visual acuity in AMD patients [46][47][48][49]. Acupuncture can reduce CMT, which may be related to the expansion of the surrounding blood vessels, thereby improving the microcirculation in the macular region [16][17][18].…”
Section: Plos Onementioning
confidence: 99%
“…In this work, we extend the applications of such an approach by constructing the classification maps for AMD. Variables such as CRT (Central Retinal Thickness) [72][73][74], GCC (Ganglion Cell Complex) thickness [75,76], MPOD (Macular Pigment Optical Den-sity) [77,78], ETDRS (Early Treatment Diabetic Retinopathy Study), Snellen and Age have been used as the descriptors and are represented on the axes of the maps. There are numerous charts used for visual acuity testing, but the most common are Snellen and ETDRS charts.…”
Section: Introductionmentioning
confidence: 99%